Empirical Evidence of Household Savings Objectives : A Demographic Comparison - Chakraborty, Suman; Digal, Sabat Kumar (Indian Journal of Finance, 2015)
Investment is one of the foremost priorities for every individual household - whether working or retired from regular service life. Investment of today would be tomorrow’s financial security. The present study made an attempt to assess households’ saving objectives and study the perceptions of respondents towards financial products that provide social security. The study is based on primary data that were collected through a survey of 567 respondents using a structured questionnaire from working as well as retired respondents in Odisha state to find out their preferred savings goals. The results showed that savings objectives significantly influenced the households to save differently as per their demographic profiles considered in the study.